CLASSIFICATION OF WORKING PLACES OF FOUNDRY PRODUCTION BY WORKING CONDITIONS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
The classification of working places of foundry production by working conditions is given.